THE REPRESENTATION OF TRUST VALUES IN RICK RIORDAN’S THE SEA OF MONSTERS - Purwarno, Purwarno; Sihaloho, Anugrah Syafrizar (JOURNAL OF LANGUAGE, 2025)
Trust is a fundamental value that shapes human interactions and relationships, providing the foundation for cooperation, loyalty, and moral responsibility. This study analyzes the representation of trust values in Rick Riordan’s Percy Jackson and the Olympians: The Sea of Monsters (2006), focusing on three dimensions identified by Mayer, Davis, and Schoorman (1995): ability, kindness, and integrity. Employing a descriptive qualitative approach, the research examines how these values are embedded in the characters’ relationships, particularly between Percy Jackson and Tyson. Primary data were collected through close reading of the novel, while secondary data were drawn from relevant scholarly literature on trust, psychology, and young adult fiction. The findings reveal that trust through ability is demonstrated by Tyson’s physical strength and Annabeth’s intelligence, which establish credibility and reliability. Trust through kindness is represented in Tyson’s loyalty and sacrifice, which transform prejudice into acceptance and deepen emotional bonds. Finally, trust through integrity distinguishes loyal characters such as Tyson and Annabeth from betrayers like Luke, highlighting the fragility of moral consistency. These representations show that trust in young adult literature serves narrative and pedagogical functions, encouraging readers to reflect on empathy, inclusivity, and ethical responsibility. The study concludes that Riordan’s novel not only entertains but also provides moral education, reinforcing the importance of trust as a transformative value in both literature and life.